BACTERIAL VAGINOSIS: STATE OF EXPLORATION OF THE PROBLEM - I. O. Makarov; M. A. Gomberg; E. L. Borovkova; L. A. Arakelyan; E. S. Berezovskaya (Акушерство, гинекология и репродукция, 2016)
In the literature review presents the status of the study of the problem of bacterial vaginosis during and outside of pregnancy, provides criteria of diagnostics and differential diagnostics, standards of treatment and prevention opportunities.